CYBERWARFARE AND RESPONSIBILITY OF STATES - Węgliński, Konrad (Torun International Studies, 2017)
The aim of this paper is to provide a general insight into the questionable nascence of the international custom in the context of cybersecurity and the most relevant attempt to draft a document regarding the subject matter from the Western perspective, taking into account the lack of any widely accepted international convention regarding the cyber security. Moreover, the paper analyzes legal requirements for finding a state responsible for a cyber attack by means of Article 2 of the ILC’s Articles on Responsibility of States for Internationally Wrongful Acts. Specifically, it analyzes legal requirements necessary to attribute a certain conduct to a state. Also, it considers if cyber attacks in general can be treated as the use of force within the meaning of article 2.4 of the UN Charter. Moreover, it examines whether the doctrine of due diligence can be used while accusing a state for a breach of its international obligations.